2015
DOI: 10.1111/rda.12514
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Mitochondria‐Associated Genes (PPARGC1A,NRF‐1,BCL‐2 and BAX) in Follicular Development and Atresia of Goat Ovaries

Abstract: Most follicles undergo atresia during the developmental process. Follicular atresia is predominantly regulated by apoptosis of granulosa cells, but the mechanism underlying apoptosis via the mitochondria-dependent apoptotic pathway is unclear. We aimed to investigate whether the mitochondria-associated genes peroxisome proliferator-activated receptor-gamma, coactivator1-alpha (PPARGC1A), nuclear respiratory factor-1 (NRF-1), B-cell CLL/lymphoma 2 (BCL-2) and BCL2-associated X protein (BAX) played a role in fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Goat GCs were collected and cultured as described previously. [ 17 ] Briefly, goat ovaries were collected from a local slaughterhouse and promptly transferred to the laboratory within 1 hour in a 0.9% saline solution. Ovaries were rinsed in 70% ethanol for 10 seconds and then washed five times with DPBS.…”
Section: Methodsmentioning
confidence: 99%
“…Goat GCs were collected and cultured as described previously. [ 17 ] Briefly, goat ovaries were collected from a local slaughterhouse and promptly transferred to the laboratory within 1 hour in a 0.9% saline solution. Ovaries were rinsed in 70% ethanol for 10 seconds and then washed five times with DPBS.…”
Section: Methodsmentioning
confidence: 99%
“…Death ligand-receptor and mitochondria-mediated apoptotic systems have been shown to be active in GCs of mammalian ovaries (Manabe et al, 2008; Zhang et al, 2015a). However, several signaling molecules involved in these systems (including JNK, Bcl-2, Bax and TRAF) are also present in the UPR and induce apoptosis (Urano et al, 2000).…”
Section: Activation Of the Upr In The Ovarian Cyclementioning
confidence: 99%
“…Banerjee and coworkers (2016) also reported that loss of C/EBPδ increased ionizing radiation and mitochondrial dysfunction, which led to antioxidant defense damage and cell apoptosis. In addition, our previous study showed that abnormal expression of NRF1 led to mitochondrial dysfunction (Zhang et al 2015). These results suggest that aberrant expression of NRF1 alters the intracellular redox balance by mitochondrial dysfunction in goat LGCs.…”
Section: Discussionmentioning
confidence: 64%
“…Downregulation of NRF1 contributes to mitochondrial dysfunction (Wang et al 2006), while overexpression of NRF1 could protect neuronal cells from MPP + -induced mitochondrial dysfunction (Piao et al 2012). Moreover, our previous study has shown that goat GCs have a reduced NRF1 expression in atretic follicles compared with healthy follicles (Zhang et al 2015). Despite these findings, the regulation of NRF1 in GC apoptosis and follicular atresia remains to be elucidated, especially in goat.…”
Section: Introductionmentioning
confidence: 97%